(untitled) (REMUNOM, 2024)
This article aims to encourage and explain how the application of International Criminal Law works, which can be conceptualized as a discipline that encompasses the set of norms and principles that typify international crimes, with the accused being judged and the guilty punished. It can also analyze, in the context of globalization, the mechanisms of international criminal justice that must act to protect human rights, with a special focus on the International Criminal Court as an important instrument for the protection of international criminal legal assets. These are contours developed to establish a specific and fully satisfactory legal doctrine for international crimes. This should establish general standards of responsibility for conduct considered crimes under International Law, systematically recording and classifying the structural elements common to such crimes.